UNIVERSAL EDUCATION: ‘A DREAM DEFERRED’? (The Pretoria Student Law Review, 2021)
This article is an analysis of the South African higher education system detailing the effects of ‘massification’ and how progress can be made in ensuring greater participation without impeding on the quality of the institutions. Bearing in mind the recent protests and the mass ‘feesmustfall’ student movement,1 higher education has become a prominent feature in the national conversation. Due to the effectiveness of higher education in breaking the poverty cycle and combating the inequalities that remain persistent in our society it is integral that access is widened more effectively especially to the most vulnerable sections of our society.
Keywords: South Africa; higher education system; massification; quality of the institutions; feesmustfall